2016
DOI: 10.4067/s0718-381x2016000200017
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes of Pregnant Women About Oral Health

Abstract: There are evidences that maternal profile, habits and health knowledge, influence in the oral health of children. The aim of this study was to assess pregnant women knowledge on oral hygiene practices and maintenance of Baby´s oral cavity. A descriptive epidemiological survey was conducted with 147 pregnant women. Sample was predominantly formed by young women and 33.33 % had incomplete primary education and most were housewives with family income between 1-2 minimum wages. Family was considered the primary me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
(13 reference statements)
1
8
1
Order By: Relevance
“…In the same line; Nogueira et al observed that about four fifths of the participated women did not attend dental clinic during pregnancy. 19 In referral to cause of not visiting dentist during pregnancy; more than two thirds of the pregnant women (68.0%) answered that dental checkup is not important during pregnancy. This may be due to that most of pregnant women keep on antenatal appointment to check fetus health status and they are not aware about the negative effect of bad oral health on their fetal health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same line; Nogueira et al observed that about four fifths of the participated women did not attend dental clinic during pregnancy. 19 In referral to cause of not visiting dentist during pregnancy; more than two thirds of the pregnant women (68.0%) answered that dental checkup is not important during pregnancy. This may be due to that most of pregnant women keep on antenatal appointment to check fetus health status and they are not aware about the negative effect of bad oral health on their fetal health.…”
Section: Discussionmentioning
confidence: 99%
“…15 Moreover; Shabbir et al recorded that less than two thirds of the pregnant women cleaned their teeth once daily while Nogueira et al recorded that the vast majority of the pregnant women brushed their teeth every day. 14,19 On the other hand; Chawla et al reported that only less than one tenth of the pregnant women brushed their teeth twice a day. 12 Findings of the current study showed that slightly more than one quarter of the pregnant women visited the dentist during the last six months; more than one half of them were suffered from painful teeth.…”
Section: Discussionmentioning
confidence: 99%
“…These results were contrasted to other studies reporting maximum number of patients 61.3% having bad taste with 62.5% bad breath, 56.2% had sensitivity, 38.8% tooth ache and 31.3% having bleeding gums. 11 The three general obstacles for not counselling dental practitioners were lack of knowledge 28%, myths like dental treatments may harm the baby 11% and financial issues in 8.5% but above all three the maximum number of 37% reported that they were unaware (Figure-2). Another study demonstrated divergent reasons like long holding up hours 53.7%, long distances 24.4% and negative attitude of medical workers 9.8%.…”
Section: Discussionmentioning
confidence: 99%
“…37,45 Age may act as a confounding factor in this context as young mothers may be more enthusiastic to learn and build a healthy attitude towards oral hygiene maintenance. 46…”
Section: Educationmentioning
confidence: 99%